Hubungan Family Support dengan Tingkat Stres pada Pasien Diabetes Melitus - Taslim, Muhammad Anis; Virka Sari, Deasy; Mirsada, Jihan Nanda (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Introduction: Diabetes Mellitus, DM, is a metabolic disease indicated by high glucose levels. Both in the world and regional levels, the prevalence of Diabetes Mellitus increases significantly. The influential factors of the disease include the increased glucose level of the patients and the family support as the supporting system to maintain the stress level stability in daily routine. The roles of families are important for Diabetes Mellitus sufferers to keep their blood glucose stable and controlled. These matters could keep recurrence. Diabetes Mellitus patients could control their blood glucose levels with the support of their families to prevent overthinking. This prevention is important to relieve the increased stress of the patients. Method: This research determined the correlation between family support and the stress level of Diabetes Mellitus patients. This cross-sectional research took 48 respondents as the samples with an accidental sampling technique. The applied statistic test was the Spearman rank test. Results: The research results showed the correlation between family support and stress level of Diabetes Mellitus patients with a p-value of 0.000 lower than 0.05. Thus, the result denies Ho and accepts Ha. The r-coefficient correlation is (-0.474), indicating a negative direct correlation. The value also indicates that the correlation is strong. Thus, high family support lowers stress levels. The researcher recommends future research to add more variables and respondents with complications in the research.